2003
DOI: 10.1111/j.1475-2743.2003.tb00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Field studies of the effects of jute geotextiles on runoff and erosion in Shropshire, UK

Abstract: Abstract. Jute geotextiles are widely used to stabilize steep banks and road cuttings. Jute protects bare surfaces until seeded grass becomes established, then after several years, the jute decays. To evaluate two types of jute geotextiles, eight erosion plots were established in July 1994 at the Hilton Experimental Site, Shropshire, UK. On 10 April 1995, the plots were treated as follows: jute geotextile net; jute mat; perennial rye grass (Lolium perenne); and bare soil, with duplicates of each treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…In similar studies, the erosion rate from jute net was found to be highly controlled by the plot slope, with high effectiveness values (99%) in case of slopes less than 30° (Kalibová et al, 2016), and with extremely low efficiency in case of steep slope (60°) (Álvarez Mozos et al, 2014). However, numerous studies have confirmed that jute net typically results in positive soil loss reduction compared to the control in both field and laboratory conditions (Mitchell et al, 2003;Álvarez Mozos et al, 2014). In a few cases (Kalibová and et al, 2017), jute net was found to increase soil loss, rather than eliminate it.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In similar studies, the erosion rate from jute net was found to be highly controlled by the plot slope, with high effectiveness values (99%) in case of slopes less than 30° (Kalibová et al, 2016), and with extremely low efficiency in case of steep slope (60°) (Álvarez Mozos et al, 2014). However, numerous studies have confirmed that jute net typically results in positive soil loss reduction compared to the control in both field and laboratory conditions (Mitchell et al, 2003;Álvarez Mozos et al, 2014). In a few cases (Kalibová and et al, 2017), jute net was found to increase soil loss, rather than eliminate it.…”
Section: Discussionmentioning
confidence: 95%
“…In Mitchell et al (2003), the higher SLRE of jute net with respect to jute mat is attributed to the fact that such a material is highly efficient at reducing infiltration during rainfall events. However, in case of long rainfall events, mats saturate, thus facilitating infiltration and soil erosion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper presents a study in which the effectiveness of three jute and coir fibre rolled erosion control systems (see Table 2), which are commercially available and widely applied worldwide, were tested under both laboratory and field conditions. No product with dense coverage (non-woven) was included, as these are not as effective in reducing run-off (Luo et al, 2013) and can produce even more run-off than bare soil (Davies et al, 2006;Mitchell et al, 2003).…”
Section: J Kalibová Et Al: the Effectiveness Of Jute And Coir Blanketsmentioning
confidence: 99%
“…Land degradation causes high erosion rates as a consequence of agriculture, grazing, mining, forest fires or deforestation and this causes economic, social and environmental damage (Cerdà, 1998;Cerdà et al, 2010;Erkossa et al, 2015;Keesstra et al, 2014;Lieskovský and Kenderessy, 2014;Moreno-Ramón et al, 2014;Stanchi et al, 2015). However, the largest erosion rates and the most degraded soils are usually found in areas affected by development, infrastructure or urbanization (Cerdà, 2007;Pereira et al, 2015;Sadeghi et al, 2015;Seutloali and Beckedahl, 2015;Yuan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%